INSTRUMEN PENILAIAN UNTUK MENGUKUR KETERAMPILAN ARGUMENTASI PADA MATERI PENCEMARAN LINGKUNGAN - Wardoyo, Kirana Wardani; Sabtiawan, Wahyu Budi (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
The purpose of this study is to analyze the feasibility of argumentation skills assessment instruments in junior high school students on environmental pollution material. In developing argumentation instruments using Toulmin's Argument Pattern model, level two argumentation indicators are claim, data, and warrant. This research uses an R&D approach to produce assessment instruments. The R&D model applied is Planning, Production, and Evaluation (PPE) from Richey & Klein. This research was tested on students of SMP Negeri in Gresik class VII A, B, and C with a total of 96 students who had received environmental pollution material. The results of logical validation and construct validation of ten questions are declared valid and suitable for use